Pharmacological Approaches to Decelerate Aging: A Promising Path. (11th July 2022) - Hassani, Bahareh; Goshtasbi, Ghazal; Nooraddini, Shirin; Firouzabadi, Negar
Abstract : Biological aging or senescence is a course in which cellular function decreases over a period of time and is a consequence of altered signaling mechanisms that are triggered in stressed cells leading to cell damage. Aging is among the principal risk factors for many chronic illnesses such as cancer, cardiovascular disorders, and neurodegenerative diseases. Taking this into account, targeting fundamental aging mechanisms therapeutically may effectively impact numerous chronic illnesses. Selecting ideal therapeutic options in order to hinder the process of aging and decelerate the progression of age-related diseases is valuable. Along therapeutic options, life style modifications may well render the process of aging. The process of aging is affected by alteration in many cellular and signaling pathways amid which mTOR, SIRT1, and AMPK pathways are the most emphasized. Herein, we have discussed the mechanisms of aging focusing mainly on the mentioned pathways as well as the role of inflammation and autophagy in aging. Moreover, drugs and natural products with antiaging properties are discussed in detail.